P041 CDKN2B-AS1 (ANRIL) expression is decreased in Inflammatory Bowel Disease epithelia and in Celiac, and its reduction is linked with induced cells proliferation. (27th May 2021) - Benshoshan, M; Sosnovski, K E; Braun, T; Amir, A; Anikster, Y; Haberman Ziv, Y
Abstract: Background: Long non-coding RNAs (lncRNAs) have attenuated expression in several immune-mediated disorders. Using mRNAseq of intestinal biopsies, we identified a widespread dysregulation of 459 lncRNAs in the ileum of treatment-naïve pediatric Crohn Disease (CD) patients. We noted that large fraction of downregulated lncRNAs were correlated with epithelial functions. CDKN2B-AS1 (ANRIL) is one of the top most down-regulated lncRNA in CD, and showed decreased expression in Ulcerative Colitis (UC) colon tissues in recent studies. Methods: Transcriptomics data is used to evaluate CDKN2B-AS1 expression in mucosal biopsies datasets and in gut epithelia. siRNA oligonucleotides targeting most CDKN2B-AS1 transcripts using Lipofectamine RNAiMAX is used to modulate CDKN2B-AS1 function, and RT-PCR to evaluate mRNA expression. xCELLigence system with gold microelectrodes in plate base is used to measure the impedance as an indicator for cell index. Results: CDKN2B-AS1 is down-regulated in bulk mucosal biopsies obtained from CD ileum [fold change (FC) -8, corrected p=1.6E-5], in UC rectum (FC -9.4, corrected p=3.9E-18), and in celiac duodenum (FC -2.3, corrected p=0.03) in comparison to controls. CDKN2B-AS1 is detected under basal conditions in HT-29 cells. Two sets of CDKN2B-AS1 siRNA oligonucleotides (targeting most transcripts) achieved up to 60% reduction in CDKN2B-AS1 expression in HT-29 cells (p=1E-04) as confirmed by RT-PCR using two sets of primers. CDKN2B-AS1 reduction significantly increased cell index as measured by xCELLigence (doubled the index, p=1.7E-03). mRNAseq of the CDKN2B-AS1 reduced HT-29, showed reduction of the tumor suppressor gene APC in CDKN2B-AS1 siRNA treated cells (FC=-1.75, p=0.04) and of TGFBR2 (FC=-1.75, p=0.04). In contrast, reduction of CDKN2B-AS1 resulted in increase in WNT11 (FC=2.1, p=0.02) and TGFB1 (FC=1.9, p=0.04), and induction of the replication associated topoisomerase TOP1MT (FC=2.7, p=0.001). We confirmed these mRNAseq results using RT-PCR. Finally, mimicking inflammation by treating HT-29 with IL1β and LPS, reduced CDKN2B-AS1 expression (by 70%, p=6.3E-04) and doubled the cell index (p=1.8E-03). Conclusion: We detected reduced CDKN2B-AS1 expression in three inflammatory disease affecting the gut in different location along the GI tract. Using HT-29 model system we were able to show, as was previously shown, an increase in cell index in CDKN2B-AS1 siRNA treated cells. We supplement those showing effect on down-stream genes that may be relevant in controlling cell proliferation. We further show that upon inflammatory triggering of HT-29 cells, CDKN2B-AS1 expression is reduced and cell index is increased, which may suggest a potential role in epithelial renewal in inflammation.